1985
DOI: 10.1002/joc.3370050608
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall analysis of the sahelian drought in the gambia

Abstract: Using rainfall data from five stations in The Gambia, it is shown that there has been a very marked decrease in annual rainfall over the last thirty years. This decrease is thought to be due to a reduction in the number of rain-producing synoptic situations rather than a decrease in intensity of rainfall.Using monthly data for the five stations and decadal and daily data for one station, it is demonstrated that the characteristics of the rainfall season have varied systematically over the years. Although the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…For Sahelian West Africa, Dennett et al (1985) reported a significant decrease in August and September rainfall amounts for the period 1941-1983 while Hutchinson (1985) also reported a similar result for the Gambia based on data analysed for the period, 1941-1982. However, it has been shown in this study that the decline in rainfall-producing situations represented by rain-days has affected all months of the Sahelian rainy season in Nigeria -July to October -from 1939 to 1985.…”
Section: Trends In Annual and Monthly Rain-days In Nigeriasupporting
confidence: 61%
See 2 more Smart Citations
“…For Sahelian West Africa, Dennett et al (1985) reported a significant decrease in August and September rainfall amounts for the period 1941-1983 while Hutchinson (1985) also reported a similar result for the Gambia based on data analysed for the period, 1941-1982. However, it has been shown in this study that the decline in rainfall-producing situations represented by rain-days has affected all months of the Sahelian rainy season in Nigeria -July to October -from 1939 to 1985.…”
Section: Trends In Annual and Monthly Rain-days In Nigeriasupporting
confidence: 61%
“…Although the trends in climatic data are seldom linear (Mitchell et al 1966), the linear regression method has been used to search for trends in many climatic time series (e.g. Ayoade 1973;Hutchinson 1985;Subbaramayya and Bhanu Kumar 1987). In testing for non-randomness in a trend, Mitchell et al (1966) suggested the use of either Mann-Kendall ('r) or Spearman (rs) rank statistics.…”
Section: The Lowpass Filter Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Short-term and long-term trends that recur regularly can thus be referred to as shortterm and long-term periodicities, respectively. A review of the literature indicates apparent evidence of rainfall trends and periodicities in West Africa (Hutchinson, 1985;Adejuwon et al, 1990;Folland et al, 1991).…”
Section: Previous Studies Of Rainfall Trends In the Sudano-sahelian Ementioning
confidence: 99%
“…The climate of the area shows considerable variability not only in annual rainfall, but also in the timing of the onset and close of the rainy season (Anyadike, 1993;Hutchinson, 1985;Department of Water Resources Records, 1950-90). It has experienced recurrent and increasingly frequent agricultural droughts during much of the 1970s and 1980s.…”
Section: Introductionmentioning
confidence: 99%